2019
DOI: 10.3389/fpsyt.2019.00542
|View full text |Cite
|
Sign up to set email alerts
|

Creating Evidence-Based Youth Mental Health Policy in Sub-Saharan Africa: A Description of the Integrated Approach to Addressing the Issue of Youth Depression in Malawi and Tanzania

Abstract: Addressing depression in young people is a health-care policy need in sub-Saharan Africa. There exists poor mental health literacy, high levels of stigma, and weak capacity at the community level to address this health-care need. These challenges are significant barriers to accessing mental health care for depression, soon to be the largest single contributor to the global burden of disease. We here describe an innovative approach that addresses these issues simultaneously while concurrently strengthening key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 34 publications
2
52
0
1
Order By: Relevance
“…Moreover, a study conducted in South Africa revealed that 94% nurses were not able to correctly recognize various disorders, including schizophrenia (Dirwayi, 2002). Despite some of these concerning statistics, some work is being carried out on enhancing MHL in sub-Saharan Africa, with at least some partial success (e.g., Kutcher et al, 2015Kutcher et al, , 2017Kutcher et al, , 2019.…”
Section: Disorder Recognition: Depression and Schizophreniamentioning
confidence: 99%
“…Moreover, a study conducted in South Africa revealed that 94% nurses were not able to correctly recognize various disorders, including schizophrenia (Dirwayi, 2002). Despite some of these concerning statistics, some work is being carried out on enhancing MHL in sub-Saharan Africa, with at least some partial success (e.g., Kutcher et al, 2015Kutcher et al, , 2017Kutcher et al, , 2019.…”
Section: Disorder Recognition: Depression and Schizophreniamentioning
confidence: 99%
“…Socioeconomic status has been associated with increased risk for depressive symptoms (Othieno et al, 2015), and higher stress levels have been associated with more substance use (Oduaran & Akanni, 2019). Poor mental health literacy and high levels of stigma appear to exacerbate the situation (Kutcher et al, 2019). For students of psychology, this stigma may be exacerbated because they may worry that they will be perceived as potentially impaired future providers of psychological services (Rummel, 2015) and fear professional isolation as well as stigma around help-seeking behaviour (El-Ghoroury, Galper, Sawaqdeh & Bufka, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health services in Kenya are under-resourced and concentrated in urban areas. To date, very few studies, particularly in African settings, have explored the causes of mental health illness among adolescents and the few that exist suggest a lack of culturally appropriate assessment tools, scarce treatment options, high stigma, and weak capacity to address this healthcare need [24]. Globally, there is suggestive but relatively limited evidence on the long-term mental health effects of large-scale disease outbreaks on children and adolescents [6].…”
mentioning
confidence: 99%